Neoergasilus japonicus (Harada) (Poecilostromatoida: Ergasilidae),a parasitic copepod new to India - Sabitha Kumari, P; Madhavi, R; Ramakrishna, R (Indian Journal of Fisheries, 2016)
The ergasilid copepod, Neoergasilus japonicus is recorded for the first time from India. It was found infectingthe fingerlings of the carp Labeo rohita in a rearing pond at Krishna District, Andhra Pradesh, India. A detaileddescription of the species is provided and also a comparison is made on the morphology of the four Indianspecies of Neoergasilus. The possibility of introduction of N. japonicus into India through exotic fish species isdiscussed.